Expression and regulation of adrenomedullin 2 gene in ovarian follicles and its effect on follicular granulosa cells in chicken - Lihong Li; Dandan Li; Qingqing Wei; Li Kang; Yi Sun; Yunliang Jiang (Poultry Science)
Adrenomedullin 2 (ADM2) is a member of the calcitonin/calcitonin gene-related peptide family and is expressed in various tissues including uterus and ovary. ADM2 is reported to play an important role in ovarian follicle development and steroidogenesis in mammals. In this study, the mRNA expression, the effects of key reproductive hormones on its expression and its effect on follicular granulosa cells were investigated. We found that the expression of ADM2 mRNA was dynamic during follicle development and was lower in the granulosa and theca cells after follicle selection. After treatment with follicle stimulating hormone (FSH), the expression of ADM2 mRNA decreased in the theca cells of pre-hierarchical follicles (Pre-TCs) and hierarchical follicles (Post-TCs), but increased in the granulosa cells of pre-hierarchical follicles (Pre-GCs) and hierarchical follicles (Post-GCs). After treatment with progesterone (P4), the expression of ADM2 mRNA decreased in Pre-TCs, Pre-GCs and Post-GCs, but increased in Post-TCs. After treatment with estradiol (E2), the expression of ADM2 mRNA increased in Post-TCs and Post-GCs. ADM2 suppressed the viability and proliferation of both Pre-GCs and Post-GCs, while facilitated their apoptosis. In both Pre-GCs and Post-GCs, ADM2 promoted the expression of genes involved in P4 synthesis (steroidogenic acute regulatory protein, StAR; cytochrome P450 family 11 subfamily A member 1, CYP11A1; 3β-hydroxysteroid dehydrogenase, 3β-HSD) and P4 secretion. These data suggest that ADM2 plays an important role by decreasing the proliferation and enhancing P4 secretion of granulosa cells around chicken follicle selection.